Hybrid approach for VATS pulmonary resection - Yamamoto, Hirotaka; Shirahashi, Koyo; Matsumoto, Mitsuyoshi; Miyamaoto, Yusaku; Doi, Kiyoshi; Iwata, Hisashi (Video-Assisted Thoracic Surgery, 2017)
Many different surgical VATS procedures are performed. In our thoracoscopic VATS, four ports are used with thoracoscopic vision alone. In our hybrid VATS, two 2-cm ports are combined with muscle-sparing mini-thoracotomy with a slightly opened metal retractor with direct vision and thoracoscopic vision. Both procedures are performed by an operator, one assistant, and a scopist. Forceps, electrocautery, and ultrasonic scissors were used. VATS segmentectomy is an ideal surgical procedure to treat primary lung cancer from the perspective of minimally invasive surgery. The most important issue in segmentectomy is to maintain a sufficient surgical margin from the tumor. We think that it is important to determine whether thoracoscopic VATS segmentectomy without direct visualization or rib spreading can achieve an adequate surgical tumor-free margin. Delicate surgery is required to keep the surgical margin in segmentectomy. Therefore, the hybrid approach seems to be reasonable for obtaining sufficient surgical margins.